Family care givers satisfaction towards nursing care of neurosurgery patients at Hospital Universiti Sains Malaysia (Hospital USM) - Shuhaidi, Nur Iliani Shuhada (Universiti Sains Malaysia, 2015)
Family caregiver’s satisfaction is one of the important elements to measure the quality of care provided by the nurses. This study to determine the family caregivers satisfaction towards nursing care of neuro patients, identify the aspects of nursing care that the most family caregivers satisfied and dissatisfied and to identify the association between selected demographic data (gender, marital status and level of education) and the family caregivers satisfaction towards nursing care of neuro patients at Hospital USM. A non-experimental and cross sectional study was used. Respondents were recruited from non-probability and purposive sampling method. Research study was carried out through the use of questionnaire which consists of two sections which are the family caregivers’ socio demographic data and the satisfaction level towards nursing care by Haya Al- Fozan (2013). The study setting involved neuro ward at Hospital USM (2 Intan, 3 Utara and 1 Selatan). There are total of forty five family caregivers participated in this study. Data collected were analysed using SPSS software version 21.0. For descriptive statistics, mean, standard deviation, frequency and percentage were used to describe the data. For inferential statistics, Pearson Chi Square and Fishers exact test were used in this study. The finding of this study shows that most of family caregivers satisfied with the nursing care provided. However there are several aspects that most family caregivers dissatisfied which are knowledge and providing information, clinical skills and caring. Most of respondents satisfied with the decision making, communication skills, family involvement and professional behaviour. There is no significant association between the selected socio demographic data and satisfaction level.